Basic measurements of radiation at station Gurgaon (2014-07 - 2019-01) - Karthik Ramanathan (PANGAEA, 2025)
This is a compilation of all short-wave and long-wave radiation datasets from Gurgaon that were published in the frame of BSRN. The data are subject to the data release guidelines of BSRN (https://bsrn.awi.de/data/conditions-of-data-release/).